Edukasi Perdagangan Berjangka dengan Pendekatan Soft-Selling bagi Ibu Rumah Tangga - Hasna, Nadya; Zawawi, Zawawi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Low financial literacy among housewives often leads to poor financial management and misconceptions about futures trading, which is commonly perceived as a high-risk or illegal activity. This community service aims to improve housewives’ understanding of futures trading concepts through a persuasive and communicative soft-selling approach. The method used was counseling and interactive discussion during a neighborhood gathering in Sidoarjo, involving 25 participants. The material, presented through the topic “One Hundred Thousand Rupiah in the Hands of the Right Wife,” emphasized practical small-capital financial management. The results show that the soft-selling approach effectively created a relaxed learning atmosphere, increased participants’ confidence, and corrected misconceptions about futures trading legality. This activity demonstrates that soft-selling can serve as an educational strategy to enhance financial literacy and empower household economies.